Locating urban conflicts : ethnicity, nationalism and the everyday - Pullan, Wendy, 1950-; Baillie, Britt, 1982- (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
"Cities have emerged as the epicentres for many of today's ethno-national and religious conflicts. In twelve multidisciplinary essays, Locating Urban Conflicts: Ethnicity, Nationalism and the Everyday brings together key themes that dominate our current political, social and cultural attention: emerging areas of contestation in rapidly changing and modernising cities, the resulting forms of habitation and spatial practice, and the effects of extreme and/or enduring conflicts upon ordinary civilian life. Such problems may be generated by larger state and regional issues to do with national identity, borders and territory, but in all cases, everyday life is regularly affected, with strong consequences for the urban arena. Section themes on Spatial Horizons, Reassessing Divisions, and Being Modern, cross-cut the research on cities in Europe and the Middle East, identifying common concerns against which the examples in this volume can be considered. Together the chapters reveal critical issues affecting ethno-national conflict in cities today"--
Machine generated contents note: -- 1. Introduction; Wendy Pullan and Britt Baillie -- 2. Spatial Discontinuities: Conflict Infrastructures in Contested Cities; Wendy Pullan -- 3. Violence and Urban Architecture: Events at the Ensemble of the Odessa Steps in 1904-5; Caroline Humphrey -- 4. Borderlands of the EU: The Spanish Enclave of Ceuta in Morocco; Felipe Hernandez and Maximilian Sternberg -- 5. Security and the Holy Places of Jerusalem: The 'Hebronisation' of the Old City and Adjacent Areas; Michael Dumper -- 6. Speaking in the Silence: Youthful Negotiations of Beirut's Postwar Spaces and Memories; Craig Larkin -- 7. Memorialising the 'Martyred City': Negotiating Vukovar's Wartime Past; Britt Baillie -- 8. Joint Israeli-Palestinian Political Activity in Jerusalem: Characteristics and Challenges; Hillel Cohen -- 9. How do Israeli (Jewish) Protest Groups Envision a Political Solution to the Jerusalem Question?; Amneh Badran -- 10. Urban Planning and the Remaking of the Public Sphere in Ottoman Palestine; Salim Tamari -- 11. Imperial Ethnocracy and Demography: Foundations of Ethno-National Conflict in Belfast and Jerusalem; James Anderson -- 12. Breaking Down the Walls of Heartache: Reflections on the Ordinary Spaces of Division and Unification in Berlin; Allan Cochrane -- 13. Territorialities of Capital and Place in 'Post-Conflict' Belfast; Milena Komarova and Liam O'Dowd.
Includes bibliographical references and index.
Keywords: Ethnic conflict; Culture conflict; National characteristics; Cities and towns; ARCHITECTURE / Urban & Land Use Planning; BUSINESS & ECONOMICS / Urban & Regional; POLITICAL SCIENCE / Civics & Citizenship; POLITICAL SCIENCE / Globalization; SOCIAL SCIENCE / Sociology / Urban